Phase II randomised trial of autologous tumour lysate dendritic cell plus best supportive care compared with best supportive care in pre-treated advanced colorectal cancer patients. (September 2016) - Caballero-Baños, Miguel; Benitez-Ribas, Daniel; Tabera, Jaime; Varea, Sara; Vilana, Ramon; Bianchi, Luis; Ayuso, Juan Ramón; Pagés, Mario; Carrera, Gemma; Cuatrecasas, Miriam; Martin-Richard, Marta; Cid, Joan; et al.
Abstract: Background: Autologous tumour lysate dendritic cell vaccine (ADC) has T-cell stimulatory capacity and, therefore, potential antitumour activity. We designed a phase II randomised trial of ADC + best supportive care (BSC) (experimental arm [EA]) compared with BSC (control arm [CA]), in pre-treated metastatic colorectal cancer (mCRC) patients. Patients and methods: Patients with progressive mCRC, at least to two chemotherapy regimens and Eastern Cooperative Oncology Group performance status (ECOG PS) 0–2, were randomised to EA versus CA. Stratification criteria: ECOG PS (0–1 versus 2) and lactate dehydrogenase (ULN). EA was administered subcutaneously till progressive disease. Primary end-point was progression-free survival (PFS) at 4 months. Results: Fifty-two patients were included (28 EA/24 CA). An interim analysis recommended early termination for futility. No objective radiological response was observed in EA. Median PFS in EA was 2.7 months (95% confidence interval [CI], 2.3–3.2 months) versus 2.3 months (95% CI, 2.1–2.5 months) in CA (p = 0.628). Median overall survival (OS) was 6.2 months (95% CI, 4.4–7.9 months) in EA versus 4.7 months (95% CI, 2.3–7 months) in CA (p = 0.41). No ADC-related adverse events were reported. Immunization induces tumour-specific T-cell response in 21 of 25 (84%) patients. Responder patients have an OS of 7.3 months (95% CI, 5.2–9.4 months) versus 3.8 months (95% CI, 0.6–6.9 months) in non-responders; p = 0.026). Conclusion: Our randomised clinical trial comparing ADC + BSC versus BSC in mCRC demonstrates that ADC generates a tumour-specific immune response but not benefit on PFS and OS. Our results do not support the use of ADC alone, in a phase III trial. Highlights: This is the first randomised clinical trial in metastatic colorectal cancer patients with autologous dendritic cells. In the experimental arm, the frequency of tumour-specific T cells increased. We were unable to demonstrate a substantial benefit in progression-free or overall survival compared with best supportive care.